2011
DOI: 10.1007/s00408-011-9301-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Nonlower Respiratory Serious Adverse Events Following COPD Exacerbations in the 4-year UPLIFT® Trial

Abstract: IntroductionChronic obstructive pulmonary disease (COPD) exacerbations are associated with systemic consequences. Data from a 4-year trial (Understanding Potential Long-term Impacts on Function with Tiotropium [UPLIFT®], n = 5,992) were used to determine risk for nonlower respiratory serious adverse events (NRSAEs) following an exacerbation.MethodsPatients with ≥1 exacerbation were analyzed. NRSAE incidence rates (incidence rate [IR], per 100 patient-years) were calculated for the 30 and 180 days before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 18 publications
(21 reference statements)
5
64
1
Order By: Relevance
“…A review of studies of patients hospitalized for COPD exacerbations found that up to 55% of patients had a history of cardiovascular disease 33. Exacerbations of COPD have a profound effect on patients’ cardiovascular status,3335 and the increase in cardiac events after the first exacerbation is irrespective of the patient’s cardiac history 36. Markers of myocardial injury, including raised troponin, chest pain, and serial electrocardiogram changes, are commonly observed in patients admitted to hospital with exacerbations of COPD 33,34.…”
Section: What Are the Likely Clinical Outcomes Of Severe Copd Exacerbmentioning
confidence: 99%
“…A review of studies of patients hospitalized for COPD exacerbations found that up to 55% of patients had a history of cardiovascular disease 33. Exacerbations of COPD have a profound effect on patients’ cardiovascular status,3335 and the increase in cardiac events after the first exacerbation is irrespective of the patient’s cardiac history 36. Markers of myocardial injury, including raised troponin, chest pain, and serial electrocardiogram changes, are commonly observed in patients admitted to hospital with exacerbations of COPD 33,34.…”
Section: What Are the Likely Clinical Outcomes Of Severe Copd Exacerbmentioning
confidence: 99%
“…Systemic inflammation is thought to accelerate atherosclerosis and thereby increase the risk of heart failure 53. In the Understanding Potential Long-term Impacts on Function with Tiotropium (UPLIFT) trial there was an increase in cardiac failure at 30 days (RR: 14.08) and 180 days (RR: 10.71) post-exacerbation 54. This risk was conferred even in those without known cardiovascular disease at baseline.…”
Section: Heart Failurementioning
confidence: 99%
“…Exacerbation of COPD is another factor affecting disease severity and has been defined as an acute event characterized by a worsening of the patient’s respiratory symptoms beyond normal day-to-day variations that leads to a change in medication [1]. Because patient recovery is often not complete after exacerbations, exacerbations have an important predictive role for COPD prognosis [5,6]. The frequency of exacerbations increases with the severity of disease and if a patient has had two or more acute events during the previous year, the patient is considered high risk [7,8].…”
Section: Introductionmentioning
confidence: 99%